Body Weight Changes of Single Comb White Leghorn Layers at Different Ages During Induced Moult - Thirunavukkarasu, P.; Moorthy, M.; Viswanathan, K. (International Journal of Poultry Science, 2007)
A study was carried out to find out the effect of induced moulting of commercial SCWL laying hens at 60, 65 and 70 weeks of age group. A control group was kept without moulting at their respective ages. The layers were reared in cages for the entire experimental period adopting standard managemental practices. The layers fed commercially available layer diet. After 28 days period of egg production (pre-moult), the layers were subjected to induced moulting by feed and water restriction followed by ad-libitum feeding and had free access to wholesome water. Seventeen hours photoperiod was provided daily through out the post-moult laying period. The birds in 70 weeks age group had higher livability among the moult induced groups and no change in body weight.